“Slam Sex” - Sexualized Injecting Drug Use (“SIDU”) amongst Men Who Have Sex with Men (MSM)—a scoping review - Scheibein, F.; Wells, J.; Henriques, S.; Van Hout, M. C. (Journal of Homosexuality, 2021)
Sexualized injecting drug use (“SIDU”) is a phenomenon associated with a wide array of high-risk injecting and sex-related practices. This scoping review establishes what is known about MSM and SIDU to assess implications for health care and policy. Characteristics of MSM for “SIDU” may include being on anti-retroviral treatment and urban residency with drivers being challenging social taboos; a search for intimacy; convenience of administration; relationship breakdown and increased restrictions in clubs and saunas. Attraction for use appears to be enhancement or prolongation of sexual experiences/pleasure; intimacy and the facilitation of a range of potentially “unsafe” sexual activity. Traditional services are ill-equipped to address “SIDU” because of a lack of knowledge of practices, lack of associated vocabulary, and a failure to integrate sexual health with drug services. For effective responses, these issues need to be addressed.